Peran Masyarakat dalam Lingkungan Bebas Jentik dengan Insiden Rate Kasus DBD di Sumut Tahun 2021 - Coni Orien; Nur Ayisah Hutabarat; Novena Sanidra Silitonga; Jatmika Nonifili Harefa (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Dengue Hemorrhagic Fever is a mosquito-borne disease that occurs in tropical and subtropical regions of the world. WHO said Dengue Hemorrhagic Fever (DHF) is an infectious disease that often occurs in tropical and subtropical regions, where this disease is a disease that can be contagious and causes death due to bleeding. For mild dengue fever, it will cause high fever and flu-like symptoms. Efforts that the community can do are to play an active role in monitoring mosquito vectors on a regular basis through the simultaneous movement to Eradicate Mosquito Nests (PSN). The PSN movement can be carried out with 3M Plus, namely firstly draining the water reservoir which can be done every 3 days or giving abate powder to kill the larvae, secondly closing the water reservoir tightly so that mosquitoes do not lay eggs, thirdly burying used items such as used cans, used tires , which can accommodate rainwater. Incidence rate (incidence rate) Is the number of all new cases in a population in a certain period. Usually the incidence rate is used for acute disease.